2022
DOI: 10.3324/haematol.2021.280016
|View full text |Cite
|
Sign up to set email alerts
|

Acute central nervous system toxicity during treatment of pediatric acute lymphoblastic leukemia: phenotypes, risk factors and genotypes

Abstract: Central nervous system (CNS) toxicity is common at diagnosis and during treatment of pediatric acute lymphoblastic leukemia (ALL). We studied CNS toxicity in 1 464 children aged 1.0–17.9 years, diagnosed with ALL and treated according to the Nordic Society of Pediatric Hematology and Oncology ALL2008 protocol. Genome-wide association studies (GWAS), and a candidate single-nucleotide polymorphism (SNP; n=19) study were performed in 1 166 patients. Findings were validated in an Australian independent cohort of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…In a study by Anastasopoulou and colleagues, patients ≥10 years of age had a higher risk of CNS toxicity than younger patients (16.3% vs. 7.4%; P <0.001). Immunophenotype (T-cell), initial CNS status as CNS III, and induction therapy (dexamethasone) were significant in univariate analyses but did not reach significance in the multivariate model, probably due to co-variation 20 . In agreement with Anastasopoulou et al, 21 older age is a risk factor for PRES, seizures, and MTX-induced CNS toxicity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a study by Anastasopoulou and colleagues, patients ≥10 years of age had a higher risk of CNS toxicity than younger patients (16.3% vs. 7.4%; P <0.001). Immunophenotype (T-cell), initial CNS status as CNS III, and induction therapy (dexamethasone) were significant in univariate analyses but did not reach significance in the multivariate model, probably due to co-variation 20 . In agreement with Anastasopoulou et al, 21 older age is a risk factor for PRES, seizures, and MTX-induced CNS toxicity.…”
Section: Discussionsupporting
confidence: 79%
“…Immunophenotype (T-cell), initial CNS status as CNS III, and induction therapy (dexamethasone) were significant in univariate analyses but did not reach significance in the multivariate model, probably due to co-variation. 20 In agreement with Anastasopoulou et al, 21 older age is a risk factor for PRES, seizures, and MTX-induced CNS toxicity. Lowe et al 22 showed that hyperleukocytosis as an indicator of high-risk disease was significantly predictive of neurological complications with a significant P value of 0.006.…”
Section: Discussionsupporting
confidence: 78%
“…Logistic regression analysis identified baseline CNS leukaemic involvement to be a significant risk for developing MTX‐induced neurotoxicity. Although paediatric patients with CNS leukaemic involvement (CNS2/3) are at higher risk of CNS toxicity, its association with MTX‐induced neurotoxicity is not well established 3,19 . Intensification of both systemic and intra‐thecal chemoprophylaxis with uniform administration of HDMTx at 5 g/m 2 for HR/VHR might have contributed to more patients developing MTX neurotoxicity in our study cohort.…”
Section: Discussionmentioning
confidence: 88%
“…Although paediatric patients with CNS leukaemic involvement (CNS2/3) are at higher risk of CNS toxicity, its association with MTX-induced neurotoxicity is not well established. 3,19 Intensification of both systemic and intra-thecal chemoprophylaxis with uniform administration of HDMTx at 5 g/m 2 for HR/VHR might have contributed to more patients developing MTX neurotoxicity in our study cohort. However, direct neurotoxic effect of leukaemic blasts and methotrexate blasts interaction contributing to MTX neurotoxicity needs to be studied.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation